Indocyanine Green to Assess Vascularity of Ileal Conduit Anastomosis During Pelvic Exenteration for Recurrent/Persistent Gynecological Cancer: A Pilot Study - Bizzarri, Nicolò; Foschi, Nazario; Loverro, Matteo; Tortorella, Lucia; Santullo, Francesco; Rosati, Andrea; Gueli Alletti, Salvatore; Costantini, Barbara; Gallotta, Valerio; Ferrandina, Gabriella; Fagotti, Anna; Fanfani, Francesco; et al. (Frontiers in Oncology, 2021)
Introduction: Pelvic exenteration performed for recurrent/persistent gynecological malignancies has been associated to urological short- and long-term morbidity, due to altered vascularization of tissues for previous radiotherapy. The aims of the present study were to describe the use of intravenous indocyanine green (ICG) to assess vascularity of urinary diversion (UD) after pelvic exenteration for gynecologic cancers, to evaluate the feasibility and safety of this technique and to assess the post-operative complications. Methods: Prospective, observational, single-center, pilot study including consecutive patients undergoing anterior or total pelvic exenteration due to persistent/recurrent gynecologic cancers between 08/2020 and 03/2021 at Fondazione Policlinico Gemelli IRCCS, Rome, Italy. All patients underwent intravenous injection of 3-6 ml of ICG (1.25 mg/ml) once the UD was completed. A near infra-red camera was used to evaluate ICG perfusion of anastomoses (ileum-ileum, right and left ureter with small bowel and colostomy or colo-rectal sides of anastomosis) few second after ICG injection. Results: Fifteen patients were included in the study. No patient reported adverse reactions to ICG injection. Only 3/15 patients (20.0%) had an optimal ICG perfusion (+++) in all anastomoses. The remaining 12 (80.0%) patients had at least one ICG deficit; the most common ICG deficit was on the left ureter: 3 (20.0%) versus 1 (6.7%) patient had no ICG perfusion (---) on the left versus right ureter, respectively (p=0.598). 8/15 (53.3%) and 6/15 (40.0%) patients experienced ≥ grade 3 30-day early and late postoperative complications, respectively. Of these, two patients had early and one had late postoperative complications directly related to poor perfusion of anastomosis (UD leak, ileum-ileum leak and benign ureteric stricture): all these cases had a sub-optimal intraoperative ICG perfusion. Conclusion: The use of ICG to intra-operatively assess the anastomoses perfusion at time of pelvic exenteration for gynecologic malignancy is a feasible and safe technique. The different vascularization of anastomotic stumps may be related to anatomical sites and to previous radiation treatment. This approach could be of support in selecting patients at higher risk of complications, who may need personalized follow up.